Two new species of Eugenia (Myrtaceae) from Central Amazonia, Brazil - de Souza, Maria Anália D.; Scudeller, Veridiana V.; de Mendonça, Maria Sílvia (Phytotaxa, 2016)
There are described, illustrated and compared with related species Eugenia lisboae and Eugenia ramosii. Eugenia lisboae is similar to E. citrifolia, differing by its adaxially concave midvein, triangular and basally connate sepals and ellipsoid fruits. Eugenia ramosii is morphologically similar to E. diplocampta, from which it differs by campto-brochidodromous venation, deltoid or scaly with acute apex and oblong-orbicular sepals that conceal the floral globe but not closing the top of bud, which is globose.